Pengaruh Peringkat Risiko ESG dan Kinerja Keberlanjutan Terhadap Nilai Perusahaan - Putri Putri; Gita Desyana; Haryono Haryono (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effect of ESG risk rating and sustainability performance on firm value in constituents that are members of the IDX ESG Leaders Index (IDXESGL) during the 2021-2023 period. A quantitative approach with purposive sampling is applied to 14 companies, resulting in 42 data observations. ESG risk ratings were measured using Sustainalytics scores, which assess a company's exposure to industry-specific material ESG risks and how well these risks are managed. Sustainability performance was assessed based on the 2021 GRI Standard disclosure index, and firm value was analyzed using Tobin's Q ratio. The multiple linear regression results show that ESG risk rating has a significant positive effect on firm value (t=3.178, p=0.003), while sustainability performance has a significant negative effect (t=-3.296, p=0.002). Collectively, the ESG risk rating and sustainability performance variables explain 47.3% (Adjusted R²=0.473) of the variation in firm value. This finding indicates that investors are more appreciative of ESG risk management, but have not fully responded positively to the implementation costs of short-term sustainability performance. This study contributes to the sustainable investment literature in Indonesia as well as strategic recommendations for companies to balance ESG practices with the dynamics of domestic capital market preferences.